DIAGNOSTIC AND THERAPEUTIC IMPLICATIONS OF ST-SEGMENT ELEVATION IN LEAD aVR OF 12 LEAD ECG DURING CHEST PAIN - Akhtar, Naveed; Bashir, Uzma; Ahmed, Waqas; Shah, Syed Mumtaz Ali (Journal of Ayub Medical College Abbottabad, 2005)
'˜aVR' is usually not the preferred lead to diagnose myocardial infarction in clinical settings, it is rather a neglected lead in this context. We describe the case of a 44 year old male who presented with short duration chest pain and ST segment elevation in lead '˜aVR'. His left heart catheterization showed left main stem equivalent disease and totally occluded right coronary artery. Patient underwent emergency coronary artery bypass-grafting with favorable outcome. This case highlights the significance of ST segment elevation in lead aVR during chest pain both in diagnosis and management of patients with acute coronary syndrome. Keywords: ST segment elevation, aVR, left main stem occlusion.